Self-expanding metallic stent placement with an exaggerated 5-cm proximal tumor covering for palliation of esophageal cancer - Tahiri, Mehdi (Ann Gastroenterol, 2015)
BACKGROUND: The study aimed to evaluate the short- and long-term outcomes with a technique of self-expanding metallic stent insertion in palliative esophageal cancer patients. We hypothesized that a systematic attempt at exaggerated (5 cm) proximal tumor covering could prevent both stent migration and tumor overgrowth/undergrowth. METHODS: We reviewed retrospectively all patients who underwent esophageal stenting for palliation of malignant dysphagia over a 24-month period. Consecutive patients were identified from a prospective thoracic surgery interventional endoscopy database. This technique consisted of endoscopic stent insertion with the aim of landing the proximal portion of the stent 5 cm cephalad to the proximal extent of the tumor. All patients were followed at one month post-procedure and every three months thereafter, until death. Short- and long-term complications associated with the procedure and mortality were evaluated. RESULTS: Forty seven patients underwent endoscopic insertion of an esophageal stent in the context of an inoperable esophageal cancer using this technique over a 24-month period. The mean age was 70.4±9.6 years. Four (8.5%) patients underwent re-stenting due to proximal tumor overgrowth. No stent migration, perforation, tumor ingrowth or stent occlusion was reported. The mean patient survival was 146±26.5 days. CONCLUSIONS: Esophageal stent insertion under endoscopic guidance with proximal tumor covering of 5 cm is effective and safe. No cases of stent migration and a low incidence of tumor overgrowth/undergrowth were observed with this technique.